ROLE OF FREE RADICALS AND EFFECTIVENESS OF ANTIOXIDANTS IN PATIENTS WITH OSMF AND OLP- A SYSTEMATIC REVIEW: Pharmaceutical Sciences-Pharmacy - VEENA NAIK, DR.; SAURABH PRAKASH, DR.; LIRIN ANN THOMAS, DR. (International Journal of Life Science and Pharma Research, 2018)
The aim of the present study is to update the evidence of antioxidants in treating oral premalignant diseases and it’s effectiveness; Data sources: automated searches of Medline, Pubmed, and the Cochrane Library were conducted; additional searches of main oral medicine journals were done manually using the keywords oral submucous fibrosis (OSF), Oral leukoplakia (OLP), treatment and antioxidants. Inclusion criteria: Surveys; randomised controlled studies (RCTs), observational studies, or case series reports that encompassed individuals of any age with confirmed diagnosis of OSF and OLP clinically and histopathologically. Types of interventions excluded were treatments with only habit intervention, surgical procedures, medical treatments (i.e. systemic, submucosal injection or topical agents), or physical therapy. 23 studies related to OLP and 15 studies related to OSF, were identified for inclusion. The authors were thoughtful in interpreting their conclusions. Treatment options included oral lycopene, oral lycopene with intralesional corticosteroids or an oral placebo; oral and topical curcumin, oral levamisole; multivitamins and oral beta carotene. Various objective and subjective outcomes improved with antioxidants, whereas some studies showed regression and malignancies. Use of antioxidants show some promise but there are no studies indicating the effectiveness of particular antioxidants or their combinations to be superior. Thus we conclude that current evidence for the benefit of antioxidants to manage OSF and OLP is weak.